TEACHING SPEAKING USING DRAMA TO IMPROVE STUDENTS’ SPEAKING SKILL AT SMK NEGERI 2 KARAWANG - Utami Ardyani Ananto; Irma Rusmiati (PROJECT (Professional Journal of English Education), 2018)
Speaking is an important role in mastering English. However, most of the students that learn English have difficulty with it. Most of the language teachers concern about the strategy in developing students’ language skill. That is why speaking has great attention among the teachers and students.. This is because speaking has important role in language learning process. In teaching speaking skill, communicative efficiency is the major goal to achieve. With the Students current skill, they should be able to make themselves understood and avoid error in understanding the message because of incorrect pronunciation, grammar or vocabulary. Therefore, teachers should have another alternative strategy to improve their students’ skill by using Drama. This research used the pre experimental method because the writer would like to find out the effectiveness of another technique in language teaching learning process. The objectives of this research entitled “Teaching Speaking using Drama” is to find out whether Drama is effective in improving students speaking skill. This research used quantitative method, the populations of this research were the third grade of SMKN 2 Karawang, while the samples were 36 students as XII Administration Office III as the participants.